Effects of angiotensin receptor-neprilysin inhibitors (ARNIs) on the glucose and fat metabolism biomarkers leptin and fructosamin. (3rd October 2022) - Ohnewein, B; Shomanova, Z; Jirak, P; Topf, A; Froeb, E J; Pogoda, C; Granitz, C; Lichtenauer, M; Hoppe, U; Reinecke, H; Pistulli, R; Motloch, L J
Abstract: Background: Heart Failure with reduced ejection fraction (HFrEF) has a life time risk about 20% among adults aged 40 years or older and a 5-year mortality rate about 60% [1, 2]. However novel therapies have shown to improve this outcome. One novel agent are angiotensin receptor-neprilysin inhibitors (ARNIs) that increase the BNP levels via inhibiting neprilsyin [3]. This has beneficial effects on heart failure by reducing preload, inflammation and fibrosis. Neprilysin also interacts with leptin and is known to correlate with the incidence and progression of heart failure if chronically elevated [4]. Furthermore beneficial affects of ARNI therapy on glucose metabolism were reported in a post-hoc analysis of the PARADIGM-HF trial [5]. In this study we aim to investigate the effect of ARNI therapy on the fat metabolism markers leptin and on the glucose metabolism marker fructosamin. Methods: In total, we included 74 patients with HFrEF with ischemic (N=37) and non-ischemic (n=37) origin in the present study. The mean NYHA class was II–III, the mean BMI 28 (SD 6.3). Patients had well established heart failure therapy before starting ARNI therapy with sacubitril/valsartan. 88% of patients were on ACE-inhibitors, 86% on beta blockers and 68% on mineralocorticoid receptor antagonists. Serum samples were obtained and analyzed for leptin, fructosamin and pBNP before and 3–6 month after ARNI therapy. The clinical parameters LVEF and NYHA class were assessed before and 3–6 month after ARNI therapy. Results: Baseline leptin level was 15.0 (SD 17.2), baseline fructosamin level was 370.1 (SD 167.7) and baseline pBNP level was 1494.9 (SD 1281.4). Under therapy a significant improvement of ejection fraction from 29, 8% to 37, 5% (7, 7 SD 8, 5 P≤0.001), an improvement of NYHA stadium from 2.46 (SD 0.62) to 1.96 (SD 0.63, p=0.005) and a significant decrease of pBNP (562.1 SD 1256.4, p=0.018) was found. Along with that, a significant increase in leptin levels (3.6 SD 8.85, p=0.012) and a significant increase in fructosamine levels (93.5 SD 160.6, p=0.013) was shown. Conclusion: Under therapy with ARNI we showed a sufficient therapy response with improvement of ejection fraction and decrease of pBNP in line with literature. Surprisingly metabolism biomarkers did significantly worsen under the first three to six month after new ARNI therapy. To distinguish between a side effect of ARNI therapy or consequence of heart failure itself further investigations are needed. Funding Acknowledgement: Type of funding sources: None.